Insulin gene polymorphisms in type 1 diabetes, Addison's disease and the polyglandular autoimmune syndrome type II - Ramos-Lopez, Elizabeth (BioMed Central, 2008)
BACKGROUND: Polymorphisms within the insulin gene can influence insulin expression in the pancreas and especially in the thymus, where self-antigens are processed, shaping the T cell repertoire into selftolerance, a process that protects from β-cell autoimmunity. METHODS: We investigated the role of the -2221Msp(C/T) and -23HphI(A/T) polymorphisms within the insulin gene in patients with a monoglandular autoimmune endocrine disease [patients with isolated type 1 diabetes (T1D, n = 317), Addison's disease (AD, n = 107) or Hashimoto's thyroiditis (HT, n = 61)], those with a polyglandular autoimmune syndrome type II (combination of T1D and/or AD with HT or GD, n = 62) as well as in healthy controls (HC, n = 275). RESULTS: T1D patients carried significantly more often the homozygous genotype "CC" -2221Msp(C/T) and "AA" -23HphI(A/T) polymorphisms than the HC (78.5% vs. 66.2%, p = 0.0027 and 75.4% vs. 52.4%, p = 3.7 × 10(-8), respectively). The distribution of insulin gene polymorphisms did not show significant differences between patients with AD, HT, or APS-II and HC. CONCLUSION: We demonstrate that the allele "C" of the -2221Msp(C/T) and "A" -23HphI(A/T) insulin gene polymorphisms confer susceptibility to T1D but not to isolated AD, HT or as a part of the APS-II.